Export Quality in Developing Countries - Henn, Christian; Papageorgiou, Chris; Spatafora, Nikola (Washington, D.C. : International Monetary Fund, 2013)
This paper develops new, far more extensive estimates of export quality, covering 178 countries and hundreds of products over 1962-2010. Quality upgrading is particularly rapid during the early stages of development, with quality convergence largely completed as a country reaches upper middle-income status. There is significant cross-country heterogeneity in quality growth rates. Within any given product line, quality converges both conditionally and unconditionally to the world frontier; increases in institutional quality and human capital are associated with faster quality upgrading. In turn, faster growth in quality is associated with more rapid output growth. The evidence suggests that quality upgrading is best encouraged through a broadly conducive domestic environment, rather than sector-specific policies. Diversification is important to create new upgrading opportunities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet